Sosialisasi Bahaya Bullying pada Siswa SMA Negeri 1 Wates Kabupaten Kediri - Zulaiha, Habibah; Harianto, Kukuh; Wardhani, Kusuma; Nurrahma, Ika (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Bullying in schools is a serious problem that negatively affects students’ psychological, social, and academic development. This community service activity aimed to raise students’ awareness of the dangers of bullying and to promote a safe and child-friendly school environment at SMA Negeri 1 Wates, Kediri Regency. The activity was conducted using a Participatory Action Research (PAR) approach through interactive socialization and counseling involving students, teachers, and school staff. The materials presented included the forms, causes, impacts, and prevention strategies of bullying in the school environment. The results showed an increase in students’ understanding of bullying, greater empathy, and stronger commitment to positive social interaction at school. This program also encouraged collaboration among schools, families, and the community to create a safe, harmonious, and character-oriented learning environment.